2008
DOI: 10.1182/blood-2007-07-099564
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped patterns of somatic hypermutation in subsets of patients with chronic lymphocytic leukemia: implications for the role of antigen selection in leukemogenesis

Abstract: Somatic hypermutation (SHM) features in a series of 1967 immunoglobulin heavy chain gene (IGH) rearrangements obtained from patients with chronic lymphocytic leukemia (CLL) were examined and compared with IGH sequences from non-CLL B cells available in public databases. SHM analysis was performed for all 1290 CLL sequences in this cohort with less than 100% identity to germ line. At the cohort level, SHM patterns were typical of a canonical SHM process. However, important differences emerged from the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
428
9
67

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 298 publications
(537 citation statements)
references
References 86 publications
(145 reference statements)
33
428
9
67
Order By: Relevance
“…37,38 However, no such bias is evident in other B-cell lymphomas, for example, CLL or MCL, where among the rearrangements using the IGHV1-2 gene, alleles *02 and *04 are detected at roughly similar frequencies. 8,24 This restricted usage of allele *04 in SMZL is noteworthy, given that it differs from allele *02 by a single amino acid, and can be considered as a molecular argument for selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 However, no such bias is evident in other B-cell lymphomas, for example, CLL or MCL, where among the rearrangements using the IGHV1-2 gene, alleles *02 and *04 are detected at roughly similar frequencies. 8,24 This restricted usage of allele *04 in SMZL is noteworthy, given that it differs from allele *02 by a single amino acid, and can be considered as a molecular argument for selection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interpretation of results for all cases was performed de novo in the context of this study, following the approaches reported in our recent publications. 8,24,28 Molecular modeling In order to explore the possible modifications in the antibody structure caused by a single amino-acid replacement---namely, the arginine (R)-totryptophan (W) substitution at position VH FR3-75 to obtain an IGHV1-2*04-rearranging antibody---we performed a molecular dynamics study of the human anti-polyhydroxybutyrate antibody F v : IGHV1-2*02 IGKV1-39*01/1D-39*01 (Protein Data Bank code 2D7T). Replacement of the VH FR3-75 R (germline for IGHV1-2*02) by the W residue (germline for IGHV1-2*04) was executed by the COOT algorithm.…”
Section: Pcr Amplification Of Ighv --Ighd --Ighj Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a biological standpoint, there are data to suggest that low mutational load in CLL productive rearrangements (leading to a germline identity of X98% but o100%) may have been functionally selected, perhaps providing the clone with certain antigenic reactivities. [15][16][17] The unproductive rearrangement would have been similarly targeted by the SHM process but remained free of any functional constraints and thus left to acquire significantly more mutations of a random nature. Whatever the underlying explanation for this phenomenon, at present, a prognostically relevant interpretation is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were diagnosed according to recently revised criteria and displayed the typical CLL immunophenotype (CD5 1 /CD19 1 /CD23 1 ) [21]. Subsets were defined according to previously described criteria [3,22] (Supporting Information Table 8S). All samples were collected at follow-up (median 82 and range 6-167 months after diagnosis) and contained 90% (average 93%) tumor cells.…”
Section: Methodsmentioning
confidence: 99%